Grice’s Conversational Implicature in Written Short Humor Dialogues - Nesya Juliana (Passage, 2015)
The present study, entitled Grice’s Conversational Implicature in Written Short Humor Dialogues examines the types of conversational implicature, hidden messages which are generated in written short humor dialogues, and audience’s responses to implicatures. The present study uses 45 written short humor dialogues which are taken from www.squackle.com, www.lotsofjokes.com, www.englishindo.com, and www.jokes4u.com. The data were analyzed qualitatively by using Grice’s conversational implicature (1975). The study is also supported by Hay’s humor support strategies (2003) to analyze the audience’s responses toward implicature. The study discovers that particularized conversational implicature is the only type of conversational implicature which appears in written short humor dialogues. Those particularized implicatures are generated through the failure in observing maxims, in the form of flouts. Moreover, flouts maxim of relation is the mostly flouted in the written short humor dialogues with 39 occurrences (86.7%) from 45 occurrences. With regard to audience’s responses, they are obtained through a short interview with 20 students from English Education Department. The result of the interviews demonstrates that the audiences only use three strategies proposed by Hay (2003) which are ‘contributing more humor’ (53%), ‘humor is support strategy itself’ (22%), and ‘mixed strategy’ (1%) between ‘contributing more humor’ and ‘offering sympathy’. All in all, the findings indicate that humors are easily made by flouting maxims. In addition, the audience’s responses signify that the humor is funny and entertaining.Keywords: Conversational Implicature, Implicature, Maxims, Audience’s responses, Written Short Humor Dialogues